Hubungan Kualitas Pelayanan Kesehatan Dengan Kepuasan Pasien Rawat Jalan di Puskesmas Hila Kabupaten Maluku Tengah Tahun 2024 - Juen Carla Warella; Nur Qalby Selayar; Nathalie E. Kailola; Ritha Tahitu; Yosepina Mainase; Lidya B. E. Sapteno; Presli Glovrig Siahaya (Jurnal Kesehatan Terpadu, 2026)
Health services are a form of service that is a basic need for every human being, because health is the main thing in supporting daily activities. Data from the World Health Organization (WHO) 2018 shows that 5.7 to 8.4 million people die due to low quality health services every year. This study aims to determine the relationship between the quality of health services and the satisfaction of outpatients at the Hila Community Health Center. This research is a quantitative analytical research. The data source comes from primary data using a cross sectional approach with Univariate and Bivariate analysis. The research results showed that on average respondents responded well to the tangible, reliability, responsiveness, assurance and empathy variables obtained during the examination at the Hila Community Health Center. The results of bivariate analysis using the chi-square test showed a P value = 0.000 (p<0.05), which means there is a relationship between the quality of health services and outpatient satisfaction at the Hila Community Health Center, Central Maluku Regency.